ME-PjBL: A Project-Based Learning Model for Mathematical Entrepreneurship to Foster an Entrepreneurial Spirit - Siti Chotimah; Jailani Jailani; Dhoriva Urwatul Wutsqa; Aditya Purnama; Sri Nurhayati (Institute of Multidisciplinary Research and Community Service, 2026)
The low level of entrepreneurial spirit among students remains a challenge for universities in producing graduates who not only possess academic competencies but are also capable of creating independent business opportunities. In mathematics education, teaching still tends to focus on mastering concepts and procedures; consequently, students’ opportunities to relate mathematical concepts to real-world problem-solving and develop entrepreneurial competencies have not yet been optimized. This study aims to analyze changes in students’ entrepreneurial spirit after taking a course using the ME-PjBL (Mathematical Entrepreneurship-Project-Based Learning) model, which integrates mathematical entrepreneurship with the Project-Based Learning model through the CREATE framework (Connect, Research, Explore, Apply, Transform, and Evaluate). The study employed a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 36 students in the Mathematics Education program. Data were collected using an entrepreneurial spirit questionnaire that included indicators of self-confidence, creativity, innovation, risk-taking, independence, cooperation and leadership, hard work, future orientation, application of mathematical concepts, and interest in entrepreneurship. Prior to use, the instrument met the criteria for content validity (Aiken’s V = 0.86) and very high reliability (Cronbach’s Alpha = 0.91). Data were analyzed using descriptive statistics and N-Gain calculations. The results showed that the average percentage of entrepreneurial spirit among students increased from 63.75% on the pretest to 89.69% on the posttest, representing an increase of 25.94% and an N-Gain value of 0.72, which falls into the high category. The indicator with the highest achievement was the application of mathematical concepts (91.67%), while the lowest achievement was in future orientation (88.19%); however, both fell into the “very good” category. These findings indicate that implementing the ME-PjBL model provides a learning experience that connects mathematical concepts with entrepreneurship-based projects and has the potential to foster students’ entrepreneurial spirit. Keywords: Mathematical entrepreneurship, Project-based learning, ME-PjBL, Entrepreneurial spirit.